Self Reliance Among Muslim Rural Community Toward Children With Disability:The Case Of School For Disabled Children Lentera Hati Nahdlotul Ulama Kecamatan Pesanggaran Kabupaten Banyuwangi - Zulfi Zumala Dwi Andriani (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2016)
Nahdlatul Ulama as the biggest Islamic mass organization in Indonesia have contributed to the educational and social welfare of Muslim especially in rural community. One of autonomous body of Nahdlatul Ulama which concern to Muslim women, Muslimat in Pesanggaran district in Banyuwangi have a special attention toward disabled children from low income family in rural community. Muslimat pesanggaran are founder of school of disabled Children (SLB)NU Lentera HAti In Pesanggaran. this study will expose the realiance of Muslimat NU pesanggaran on giving special attenction toward disabled children. the main data is the SLB NU Lentera Hati,the collected data came from depth interview of some teachers, Muslimat board and some social activist in Banyuwangi. The study concluded that every body has the responsibility on helping each other especially toward disabled children. what have been done by Muslimat in Pesanggaran should be followed by any support of government and any other organization so that every disabled children have the opportunity to get their educational rights